From Stability to Power Projection: An Analysis of Indonesia’s Shifting Foreign Policy Orientation during the Reigns of Joko Widodo and Prabowo Subianto - Sitepu, Qory Fizrianti Beru (Hasanuddin Journal of International Affairs, 2025)
The leadership transition from President Joko Widodo to President Prabowo Subianto marked a change in the style and direction of Indonesia’s foreign policy. These changes are influenced by the domestic interests and personal character of each leader in making various political decisions that are important for Indonesia globally. This difference is essential to analyse, especially in the midst of rising global geopolitical tensions, multipolarity challenges, and pressing national needs. Therefore, this study raises the research question of why Indonesia’s foreign policy orientation at the beginning of President Prabowo Subianto’s administration shifted in approach compared to the era of President Joko Widodo’s administration? To answer the research question, this article utilises Gideon Rose’s Innenpolitik theory, finding that the foreign policies produced by the two leaders were based on domestic configurations, including political and economic ideology, national character, and socio-economic structure. Through a qualitative approach with narrative analysis, this article also finds that personal interpretations formed from background, professional experience, and individual characteristics influence the foreign policy orientation of the two leaders.